2021
DOI: 10.1111/cpf.12722
|View full text |Cite
|
Sign up to set email alerts
|

There are no differences in brachial artery endothelial shear stress and blood flow patterns between males and females during exercise

Abstract: Premenopausal females have a lower cardiovascular risk than males. Sex differences on exercise‐induced endothelial shear stress (ESS) and blood flow patterns may explain part of this risk reduction. The purpose of this cross‐sectional study was to determine the differences in brachial artery exercise‐induced ESS and blood flow patterns between males and females. Thirty subjects (13 females) were recruited to perform a three‐workload steady‐state exercise test based on blood lactate levels (i.e. <2.0, 2.0–4.0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
1
8
2
Order By: Relevance
“…Finally, the results of the current study showed no sex differences in any of the exercise modalities at any of the intensities. This is consistent with previous findings from our laboratory when assessing the brachial artery during cycle-ergometry at low, moderate, and high intensities ( Gurovich et al, 2021b ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Finally, the results of the current study showed no sex differences in any of the exercise modalities at any of the intensities. This is consistent with previous findings from our laboratory when assessing the brachial artery during cycle-ergometry at low, moderate, and high intensities ( Gurovich et al, 2021b ).…”
Section: Discussionsupporting
confidence: 93%
“…During sub-maximal exercise sets (sessions 3 and 4), real-time carotid artery longitudinal images and blood flow velocity were recorded with a 12 MHz ultrasound transducer and Doppler, (LA435, MyLab30 Gold, Esaote, Firenze, Italy), which has secure with a cervical probe holder placed on the participant’s neck as previously described ( Gurovich et al, 2021b ; Morales-Acuna et al, 2020 ). Ultrasound images and Doppler signals were obtained on the common carotid artery 2 cm below the bifurcation of the anterior and posterior carotid arteries and then analyzed with edge detection technology (Vascular Analysis Integrative System, Medical Imaging Applications, Coralville, IA, United States) and a data acquisition system (MP150WSW, BIOPAC Systems Inc., Goleta, CA, United States) ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we must validate the framework's utility by comparing its efficacy and safety to other assay methods in randomized clinical trials. In a forthcoming work, we will evaluate the effect of aerobic exercise on the risk of developing blood coagulation disorders using data collected from real subjects [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The results of the present study challenge this paradigm. On the one hand, and based on in vivo data, 16,26 endothelial shear stress observed in the bifurcated slide would have produced significant turbulent flow at the bifurcation. On the other hand, changes in actin expression showed beneficial effects of turbulent flow at the bifurcation site.…”
Section: Discussionmentioning
confidence: 99%